Development of a Digital Transformation Roadmap for Urban Water Supply Utilities - Grove, J. B.; Jooste, J. L.; Lucke, D. M.; Zincume, P. N. (International ICE Conference on Engineering, Technology and Innovation (Online), 2024)
This paper provides strategic guidance through the development of a structured and systematic roadmap to support urban water supply utilities with the process of digital transformation. The roadmap design requirements are established and refined through a state-of-the-art literature review and empirical investigation utilizing semi-structured interviews with subject matter experts. The research identifies seven distinct roadmap phases to be completed in an agile, continuous, and iterative manner to better navigate the complex landscape of digital transformation. In particular, each of the respective roadmap phases is characterized by distinct objectives and equipped with practical tools enabling water supply utilities to exploit the potential of digital transformation according to their individual requirements and characteristics. Finally, the roadmap is verified and substantiated by performing face validation through semi-structured interviews.